Classification of p¯+ p induced reactions - Dbeyssi, A.; Tomasi-Gustafsson, E. (Вопросы атомной науки и техники, 2012)
Annihilation cross sections of antiproton-proton into hadronic channels are studied and related experimental data are compiled. These channels constitute a high source of background to the annihilation reactions p¯+ p → l⁺ + l⁻, p¯+p → l⁺ + l⁻ + π⁰, used for the measurement of proton form factors in Time-like region. Pion multiplicity in final state is also analysed, since the 2 neutral or charged pion production is expected to be an important issue in the detection of the leptons pair.